Shaping BiodiverCities a research institute for city biodiversity conservation utilizing animal-building integration - Go, Gillian Gabrielle Therese O. (College of Architecture, University of the Philippines Diliman, 2025)
The Philippines, a rapidly urbanizing South East Asian country, is projected to have around 102 million city dwellers by 2050. Important questions arise: Can biodiversity continue to exist in cities? Can cities and the built environment be designed in ways that support the conservation and sustainable use of its biodiversity? As city biodiversity conservation is still an emerging field, this project aims to design a research institute in Quezon City focused on this issue. The institute utilizes animal-building integration strategies, and increases public green spaces to support city biodiversity. Data for the project were gathered through key informant interviews, site visits, activity mapping, survey questionnaire, and secondary sources. These were analyzed using frequency analysis, site selection criteria, and according to themes, user behaviors, and study of space. Birds are the project's flagship species and the primary taxonomic group, which provides a strong foundation for integrating wildlife into the project design. The proposed research institute consists of two main structures: the Public Education Center and the Research Building with a Maintenance Annex. Each structure serves a distinct role, collectively supporting the broader goal of conservation. Architectural strategies for animal-building integration are expressed through hexagonal building forms and animal-aided design features. These include nesting façade modules, constructed wetlands, and insect hotels to support the life cycle needs of birds. A vegetated overhead walkway links the site to the Ninoy Aquino Parks and Wildlife Center, promoting pedestrian movement and enhancing ecological connectivity for species between green spaces.